Role of deposition strategy and fill depth on the tensile and fatigue performance of 300 M repaired through laser directed energy deposition. (May 2021) - Barr, Cameron; Rashid, Rizwan Abdul Rahman; Da Sun, Shi; Easton, Mark; Palanisamy, Suresh; Orchowski, Nicholas; Matthews, Neil; Walker, Kevin; Brandt, Milan
Highlights: Tensile strength decreases with repair depth, but fatigue life remains similar. Additive technique equivalent to current grind-out method for low cycle fatigue. High cycle fatigue lower due to defects and local softening via in-situ tempering. Layer delay strategy for in-situ tempering out performs track delay method. Track delay leads to severe localised cracking at soft bands between tracks. Abstract: Laser directed energy deposition repair provides significant advantage over current grind-out repair methods for 300 M steel, with samples containing 40% deposit producing equivalent low cycle fatigue behaviour to unfilled 10% grind-outs, though with reduced tensile strength. High cycle fatigue is associated with crack initiation at defects or locally softened regions due to in-situ tempering. While deposition strategy influences the degree of tempering, both layer and track delay strategies produce equally soft regions leading to similar fatigue limits regardless of fill depth. Layer delay specimens perform better overall due to more uniform tempering, which prevents concentrated crack growth and premature failure.